2021
DOI: 10.3389/fpsyt.2021.766804
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Bullying Victimization Among 170,618 Adolescents in 59 Countries

Abstract: Background: Bullying victimization can impose long-lasting impacts on adolescent's current and subsequent well-being. Understanding the correlates of bullying victimization and how to prevent its occurrence is an urgent need. Food insecurity, an indicator of low socioeconomic status, may be related to bullying victimization. However, research on the association between food insecurity and bullying victimization is limited. Using a representative global sample, this study aimed to investigate the association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
2
5
0
Order By: Relevance
“…In this study gender was associated with food insecurity, with males being significantly more affected than females. This is similar to findings from previous studies among adolescents in both developed and developing countries (Sheikh et al, 2020;Liang et al 2021;Yeh et al, 2021). It may be an indication of the influence of gender norms on the protection of girls from the adverse consequences of household food insecurity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study gender was associated with food insecurity, with males being significantly more affected than females. This is similar to findings from previous studies among adolescents in both developed and developing countries (Sheikh et al, 2020;Liang et al 2021;Yeh et al, 2021). It may be an indication of the influence of gender norms on the protection of girls from the adverse consequences of household food insecurity.…”
Section: Discussionsupporting
confidence: 92%
“…This implies that the prevention of alcohol and other drug use among adolescents may very well need to address food insecurity to be successful. Similar to previous studies, there was an association between food insecurity and history of fights as well as bullying (victimization) among the adolescents studied (Peltzer & Pengpid, 2017; Seidu et al, 2020; Liang et al, 2021). These findings buttress the views of previous researchers on the influence of food insecurity on adolescents” psychosocial wellbeing.…”
Section: Discussionsupporting
confidence: 87%
“…Regarding the direct effects, our findings show a positive association between family financial struggle and children's bullying victimization, which was consistent with our hypothesis and previous research findings (Alikasifoglu et al, 2007; Chen et al, 2021; Jansen et al, 2011; Lien & Welander‐Vatn, 2013; Napoletano et al, 2016; Woolweaver et al, 2022). Children whose families are struggling financially are not only lacking necessary economic resources but also experiencing adversities such as inadequate hygiene and food insecurity, which are significant risk markers for bullying victimization and teasing by peers (Liang et al, 2021; Murshid, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that social factors may also have a significant effect on bullying victimization. For instance, Liang et al reported that adolescents in countries with food insecurity were more likely to be victims of bullying, with an odds ratio (OR) of 1.37 [ 17 ]. In addition, Deryol et al observed that countries with high inequality-adjusted Human Development Index (HDI) had a lower prevalence of bullying victimization [ 18 ].…”
Section: Introductionmentioning
confidence: 99%